2022
DOI: 10.3390/antiox11122364
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties, Bioactivity and Health Effects of Indicaxanthin, a Bioavailable Phytochemical from Opuntia ficus indica, L.: A Critical Review of Accumulated Evidence and Perspectives

Abstract: Phytochemicals from plant foods are considered essential to human health. Known for their role in the adaptation of plants to their environment, these compounds can induce adaptive responses in cells, many of which are directed at maintaining the redox tone. Indicaxanthin is a long-known betalain pigment found in the genus Opuntia of cactus pear and highly concentrated in the edible fruits of O. ficus indica, L. whose bioactivity has been overlooked until recently. This review summarizes studies conducted so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 256 publications
(468 reference statements)
0
4
0
Order By: Relevance
“…In this context, the genus Opuntia spp., belonging to the Cactaceae family, represents a group of plants of great interest for several reasons. On the one hand, these plants are a great source of numerous compounds, such as polyphenols, betalains and pectins, among others, that can induce beneficial effects on human health [ 9 , 10 , 11 , 12 ]. On the other hand, climate change is causing global warming and drought, and in this scenario, Opuntia spp.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the genus Opuntia spp., belonging to the Cactaceae family, represents a group of plants of great interest for several reasons. On the one hand, these plants are a great source of numerous compounds, such as polyphenols, betalains and pectins, among others, that can induce beneficial effects on human health [ 9 , 10 , 11 , 12 ]. On the other hand, climate change is causing global warming and drought, and in this scenario, Opuntia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Betalains are water-soluble, nitrogen-containing, vacuolar molecules that are synthesized as secondary plant metabolites that respond to adverse exogenous conditions [4]. They can be classified into two groups depending on their structural interaction with Foods 2024, 13, 1003 2 of 28 betalamic acid: betaxanthins, which are formed by conjugation with different amino acids and provide yellow-orange tones, with indicaxanthin (proline-betaxanthin) being the most abundant, as well as betacyanins, which are formed by condensation with cyclo-dopa or its glycoside derivatives and give rise to red-violet colorings, of which betanin stands out [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated to possess a quite large (>50%) non-polar surface that provides it with an amphipathic character. This could facilitate the intestinal absorption of this molecule regarding others betalains, due to its easy access into cells and its incorporation into the brain-blood barrier (study carried out in rat brains) [4]. Gómez-Maqueo et al [3] analyzed indicaxanthin's bioaccessibility from Opuntia ficus-indica fruit extracts and reported values of 58 ± 5% for Colorada (yellow-orangish variety) and of 70.7 ± 3.2% for Morada (purple variety), while Montiel-Sánchez et al [10] reported values of 15 ± 9% for indicaxanthin from Myrtillocactus geometrizans berries.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural compounds isolated from plant material are screened in order to check their pharmacological activities. Extensive research on these compounds demonstrates that they exhibit a wide spectrum of actions against human diseases as well as biological activities [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%